ADAMTS9-AS1 Constrains Breast Cancer Cell Invasion and Proliferation via Sequestering miR-301b-3p - Chen, Junqing; Cheng, Ling; Zou, Weibin; Wang, Rong; Wang, Xiaojia; Chen, Zhanhong (Frontiers in Cell and Developmental Biology, 2021)
Objective: For determination of how ADAMTS9-AS1/miR-301b-3p/TGFBR2/JAK STAT signaling axis modulates progression of breast cancer cells. Methods: Target lncRNA was determined by differential analysis of breast cancer expression data and survival analysis. Differentially expressed miRNAs and target mRNAs that had binding sites with target lncRNA were predicted. GSEA software was used to carry out pathway enrichment analysis for mRNAs. Binding of the researched genes were tested with RNA binding protein immunoprecipitation (RIP). How miR-301b-3p bound TGFBR2 mRNA was tested by dual-luciferase method. Transwell, colony formation, EdU approaches were employed for verification of invasion and proliferation of breast cancer cells in each treatment group. Results: Markedly inactivated ADAMTS9-AS1 in breast cancer pertained to patient’s prognosis. MiR-301b-3p was capable of binding TGFBR2/ADAMTS9-AS1. However, overexpression of ADAMTS9-AS1 stimulated miR-301b-3p binding ADAMTS9-AS1 and repressed miR-301b-3p binding TGFBR2 mRNA. ADAMTS9-AS1 interference enhanced cancer proliferation and invasion, facilitated levels of KI67, PCNA, MMP-9 and MMP-2, and activated the JAK STAT signaling pathway. While silencing miR-301b-3p reversed the effect of ADAMTS9-AS1 interference. In addition, TGFBR2 interference or restraining JAK STAT signaling counteracted the effect of ADAMTS9-AS1. Conclusion: ADAMTS9-AS1 could sequester miR-301b-3p to inhibit progression of breast cancer via TGFBR2/JAK STAT pathway. This study supplies a rationale for incremental apprehension of ADAMTS9-AS1 in breast cancer progression.